Wheat Selenium-binding protein TaSBP-A enhances cadmium tolerance by decreasing free Cd2+ and alleviating the oxidative damage and photosynthesis impairment - Luo, Fei; Zhu, Dong; Sun, Haocheng; Zou, Rong; Duan, Wenjing; Liu, Junxian; Yan, Yueming (Frontiers in Plant Science, 2023)
Cadmium, one of the toxic heavy metal, robustly impact crop growth and development and food safety. In this study, the mechanisms of wheat (Triticum aestivum L.) selenium-binding protein-A (TaSBP-A) involved in response to Cd stress was fully investigated. As a cytoplasm protein, TaSBP-A showed a high expression in plant roots and its expression levels were highly induced by Cd treatment. The overexpression of TaSBP-A enhanced Cd-toleration in yeast, Arabidopsis and wheat. Meanwhile, transgenic Arabidopsis under Cd stress showed a lower H2O2 and malondialdehyde content and a higher photochemical efficiency in the leaf and a reduction of free Cd2+ in the root. Transgenic wheat seedlings of TaSBP exhibited an increment of Cd content in the root, and a reduction Cd content in the leaf under Cd2+ stress. Cd2+ binding assay combined with a thermodynamics survey and secondary structure analysis indicated that the unique CXXC motif in TaSBP was a major Cd-binding site participating in the Cd detoxification. These results suggested that TaSBP-A can enhance the sequestration of free Cd2+ in root and inhibit the Cd transfer from root to leaf, ultimately conferring plant Cd-tolerance via alleviating the oxidative stress and photosynthesis impairment triggered by Cd stress.